AVALIAÃ‡ÃƒO DO EFEITO DE ACARICIDAS SOBRE ÃCAROS PREDADORES (PHYTOSEIDAE) E OUTROS ARTRÃ“PODOS EM CITROS - Sato, MÃ¡rio Eidi; CerÃ¡volo, Leonardo Coutinho; Rossi, Antonio Carlos; CezÃ¡rio, Antonio Carlos; Potenza, Marcos Roberto; Raga, Adalton (REVISTA DE AGRICULTURA, 2020)
AVALIAÃ‡ÃƒO DO EFEITO DE ACARICIDAS SOBRE ÃCAROS PREDADORES (PHYTOSEIDAE) E OUTROS ARTRÃ“PODOS EM CITROS